The Comparison of the Formation of Indonesian and Arabic Plural Meanings (Contrastive Analysis) - Sofia Nur Khasanah; Imam Baehaqie (JURNAL ARBITRER, 2021)
This study compares the process of forming plural words in Indonesian and Arabic to determine the similarities and differences in the markers of the two languages' plural meaning through contrastive analysis studies. The data in this study are fragments of speech that are thought to contain plural meaning. They are taken from the source of data in the form of speech that contains plural meanings in the two languages' books. The data are analyzed using the split method with the Direct Element Dividing technique and the equivalent method using the Determination Element Determination technique. This study indicates that the formation of plural languages in Indonesian and Arabic has similarities and differences in rules. The equation includes the addition of affixes, numeral, plural lexical meanings, and changes in pronouns. The differences in the rules of the formation of plural words of Indonesian and Arabic include reduplication, internal modification, the existence of dualistic forms, gender differences in words, case differences, and subject-predicate relationships.